2016
DOI: 10.1158/1557-3265.pdx16-pr03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PR03: Characterizing the immune context of responses to immunotherapy in humanized patient derived xenograft models of CRC

Abstract: Introduction: Inhibiting the activity of the epidermal growth factor receptor (EGFR) with monoclonal antibodies has been utilized as a therapeutic strategy for patients with metastatic colorectal cancer (CRC), leading to improved clinical results alone and in combination with standard chemotherapy. Many systematic reviews and metanalyses were performed to better understand the role of EGFR inhibition in CRC, revealing that KRAS exon 2 mutations and furthermore exons 3 and 4 and NRAS exons 2, 3, and 4 were pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been shown that tumors with MSI and hypermutation display high degrees of immune infiltration with cytotoxic T lymphocytes, activated helper T cells, and natural killer cells [158,159], and these subsets of CRC selectively have high expression levels of multiple immune checkpoints, including PD-1, PD-L1, CTLA-4, LAG-3, and IDO [160,161]. Preliminary studies demonstrated that human immune cells and PD-1-expressing T cells are present in humanized PDX models of CRC [162,163]. Furthermore, in vivo MSI-high and microsatellite-stable (MSS) humanized CRC PDXs have been successfully established [164], and, as expected, characterization of these models confirmed higher levels of immune infiltrates and improved response to the PD-1 inhibitor, nivolumab, in MSI-high PDX models compared to MSS PDX models.…”
Section: Humanized Pdx Models Link Msi and Immunotherapy Response mentioning
confidence: 99%
“…It has been shown that tumors with MSI and hypermutation display high degrees of immune infiltration with cytotoxic T lymphocytes, activated helper T cells, and natural killer cells [158,159], and these subsets of CRC selectively have high expression levels of multiple immune checkpoints, including PD-1, PD-L1, CTLA-4, LAG-3, and IDO [160,161]. Preliminary studies demonstrated that human immune cells and PD-1-expressing T cells are present in humanized PDX models of CRC [162,163]. Furthermore, in vivo MSI-high and microsatellite-stable (MSS) humanized CRC PDXs have been successfully established [164], and, as expected, characterization of these models confirmed higher levels of immune infiltrates and improved response to the PD-1 inhibitor, nivolumab, in MSI-high PDX models compared to MSS PDX models.…”
Section: Humanized Pdx Models Link Msi and Immunotherapy Response mentioning
confidence: 99%